Spiritual Care in Public Institution in Europe, eds. Jiří Rajmund Tretera and Záboj Horák. Berlin: Berliner Wissenschafts-Verlag, 2019, 140 pp. - Menke, Monika (Philosophy and Canon Law, 2021)
Spiritual Care in Public Institution in Europe, eds. Jiří Rajmund Tretera and Záboj Horák. Berlin: Berliner Wissenschafts-Verlag, 2019, 140 pp.